The effect of work-life balance and supervisor support on turnover intention and its impact on employee performance - Nugroho, Ageng; Sudrajat, Enjat; Wulandhari, Otti (Institute of Computer Science (IOCS), 2024)
The productivity level of the Indonesian population as an outcome of performance has not been able to compete with ASEAN's productivity. The low performance of this population is caused by various factors, including the imbalance between work and personal life and the lack of leadership involvement in employee well-being. These two factors not only affect company performance but also lead to employees' desire to leave their jobs, which is why this study was conducted. This research aims to determine whether there is a positive and negative effect of work-life balance and supervisor support on employee performance with or without mediation from turnover intention. From this study, it was found that there is a negative effect of work-life balance on employee performance, and a negative effect of turnover intention on employee performance was also found. There is a positive effect of work-life balance on turnover intention. It was found that there is no effect of supervisor support on turnover intention. Additionally, a positive effect of supervisor support on employee performance was found in this research. Moreover, it was found in this study that turnover intention mediates the effect of work-life balance on employee performance, while turnover intention cannot mediate the effect of supervisor support on employee performance.